2007
DOI: 10.1074/jbc.m703108200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Autoxidation Products of the ω-3 Fatty Acid Eicosapentaenoic Acid in Vitro and in Vivo

Abstract: Increased intake of fish oil rich in the -3 fatty acids eicosapentaenoic acid (EPA, C20:5 -3) and docosahexaenoic acid (DHA, C22:6 -3) reduces the incidence of human disorders such as atherosclerotic cardiovascular disease. However, mechanisms that contribute to the beneficial effects of fish oil consumption are poorly understood. Mounting evidence suggests that oxidation products of EPA and DHA may be responsible, at least in part, for these benefits. Previously, we have defined the free radical-induced oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…The fragmenta-tion patterns of A 3 /J 3 -IsoPs are similar to F 3 -IsoPs, and, indeed, previously acquired information regarding the F 3 -IsoPs was extremely useful for the present work (16). In addition, based on previous studies with F 3 -IsoPs, we would hypothesize that the 5-series and 18-series A 3 /J 3 -IsoPs should predominate, given the ability of the other 4-series of A 3 /J 3 -IsoP regioisomers to further oxidize to yield novel dioxolane-IsoPs derived from EPA (22). But, as is evident from data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragmenta-tion patterns of A 3 /J 3 -IsoPs are similar to F 3 -IsoPs, and, indeed, previously acquired information regarding the F 3 -IsoPs was extremely useful for the present work (16). In addition, based on previous studies with F 3 -IsoPs, we would hypothesize that the 5-series and 18-series A 3 /J 3 -IsoPs should predominate, given the ability of the other 4-series of A 3 /J 3 -IsoP regioisomers to further oxidize to yield novel dioxolane-IsoPs derived from EPA (22). But, as is evident from data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fish oil supplementation on levels of A 2 -/J 2 -IsoPs derived from arachidonic acid oxidation was also studied, and we found that EPA supplementation significantly reduced their level of formation (p Ͻ 0.05, data not shown). In addition, it should be noted that we have previously undertaken studies to confirm the stability of EPA in the fish oil diet fed to rodents to ensure that the source of oxidized EPA products was not the diet and that they were generated in vivo (22). techniques have been developed to analyze intact phospholipids as well as oxidized phospholipids (23)(24)(25)(26)(27)(28).…”
Section: Formation and Characterization Of A 3 /J 3 -Isops In Vitro-mentioning
confidence: 99%
“…In contrast, recent studies on the effects of prostaglandins (PGE 2 and PGE 3 ) and leukotrienes (LTB 4 and LTB 5 ) on endothelium permeability and mononuclear adhesion and migration across endothelial cell cultures indicate that PGE 3 produces more pronounced effects on trans-endothelial Evans blue-albumin (EBA) permeability than PGE 2 , and these effects are antagonized by EP 1 and EP 2 antagonists (Moreno, 2009). LTB 4 and LTB 5 produce a slight effect on EBA extravasation (Moreno, 2009;Yin et al, 2007). It is suggested that EPA and ARA compete for the same COX enzymes (Zhao et al, 2004;Phillis et al, 2006), but the rate of oxidation of EPA is only 10% of the ARA.…”
Section: Epa-derived Lipid Mediators In the Brainmentioning
confidence: 85%
“…Since EPA has five carbon double bonds in its structure, it is readily oxidized to various oxidation products in food and the human body 16,17 . Lipid oxidation has been proposed to be harmful to human health and food quality.…”
Section: Introductionmentioning
confidence: 99%